Stability analysis of concrete gravity dams under uncertainty (REC 2026 - 11th International Workshop on Reliable Engineering Computing: Reliability Computations in a Data and Model-Driven World, 2026)
The stability analysis of concrete gravity dams is challenging due to uncertainties in shear strength parameters and external loads. Conventional crack-based Limit Equilibrium Methods (LEM), which rely on the linear Mohr–Coulomb (MC) shear strength model, often yield conservative results because they neglect nonlinear strength gain from joint roughness and dilation. Probabilistic approaches, such as Monte Carlo Simulation (MCS), provide useful statistical insight but require extensive site-specific data and probability distributions that are rarely available for existing old dams. This work presents an Interval Finite Element Method (IFEM) framework for sliding stability assessment under parameter uncertainty. The method integrates interval arithmetic with the nonlinear Barton–Choubey (BC) shear strength model, an element-by-element assembly strategy to reduce dependency effects, and an interval crack initiation and propagation criterion driven by tensile- and shear-stress conditions. External load (uplift pressure) and boundary conditions are updated iteratively as the crack propagates. All uncertain parameters, including Young's modulus, density, Barton-Choubey shear strength parameters, are expressed as intervals and incorporated into the IFEM framework. The framework is validated through a concrete gravity dam case study using laboratory data, historical temperature records, and construction photographs. Results show that the dam remains stable with interval safety factors consistently above unity and crack lengths closely matching Monte Carlo Simulation (MCS) predictions, while avoiding the excessive safety margins characteristic of LEM. The proposed IFEM approach provides reliable, computationally feasible, and data-efficient safety bounds suitable for dams with limited site information.